Management of Olive-Mills Wastewater in Palestine - Hafez Shaheen; Riyad Abdel Karim (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Different treatment technologies are reported to have been applied for treating olive-mills wastewater (OMW). Among these are the anaerobic combined with aerobic, forced evaporation, chemical, and biological treatment methods. The reuse of the solid residue of olive-mills is reported, among others, as burning material or as filtering media. This paper evaluates the treatment options of the OMW generated in Palestine. It elaborates on the different treatment and management alternatives and examines their effectiveness. A sample of 20 Mills has been surveyed in the Nablus-Tulkarem region and their wastewater quantities and characteristics are presented. Centralized treatment and disposal plants for OMW are recommended as a practical option for Palestine. Oil-extraction process modifications in combination with forced evaporation are recommended as the most appropriate management and treatment option.